2020
DOI: 10.1177/2164956120964712
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Month Whole-Systems Ayurvedic Medicine Nutrition and Lifestyle Intervention Is Feasible and Acceptable for Breast Cancer Survivors: Results of a Single-Arm Pilot Clinical Trial

Abstract: Purpose Ongoing symptoms and impairments in quality of life (QOL) among breast cancer survivors remain a significant problem. We tested the feasibility and acceptability of a manualized Ayurvedic nutrition and lifestyle intervention for breast cancer survivors. Methods Eligible participants had Stage I–III breast cancer, underwent treatment within the past year that included chemotherapy, and were without active disease. The 4-month individualized Ayurvedic intervention included counseling on nutrition, lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A good clinical representation of the holistic approach of Ayurveda in clinical trials for cancer was a whole systems nutrition and lifestyle intervention for breast cancer survivors [ 41 ]. This study showed the feasibility and acceptability of an Ayurvedic intervention and measured symptoms and quality of life outcomes.…”
Section: Mechanistic and Clinical Studies In Ayurvedic Herbsmentioning
confidence: 99%
“…A good clinical representation of the holistic approach of Ayurveda in clinical trials for cancer was a whole systems nutrition and lifestyle intervention for breast cancer survivors [ 41 ]. This study showed the feasibility and acceptability of an Ayurvedic intervention and measured symptoms and quality of life outcomes.…”
Section: Mechanistic and Clinical Studies In Ayurvedic Herbsmentioning
confidence: 99%
“…Yoga was found to reduce depression and fatigue in cancer patients with the greatest benefit to breast cancer patients [ 58 ]. Yoga was part of a multi-modality Ayurvedic nutrition and lifestyle intervention program in breast cancer survivors [ 59 ] which explored the feasibility and potential benefit of this approach to reducing symptoms of fatigue, sleep disturbance, anxiety, depression, and perceived stress. The study concluded that the Ayurvedic intervention may “contribute to clinically meaningful improvements in this survivorship population which merits future study in a randomized control trial”.…”
Section: The Role Of the Mind Body And Spiritmentioning
confidence: 99%